Angiogenic factor AGGF1 acts as a tumor suppressor by modulating p53 post-transcriptional modifications and stability via MDM2. (28th January 2021) - Si, Wenxia; Zhou, Bisheng; Xie, Wen; Li, Hui; Li, Ke; Li, Sisi; Deng, Wenbing; Shi, Pengcheng; Yuan, Chao; Ke, Tie; Ren, Xiang; Tu, Xin; et al.
Abstract: Angiogenesis factors are widely known to promote tumor growth by increasing tumor angiogenesis in the tumor microenvironment, however, little is known whether their intracellular function is involved in tumorigenesis. Here we show that AGGF1 acts as a tumor suppressor by regulating p53 when acting inside tumor cells. AGGF1 antagonizes MDM2 function to inhibit p53 ubiquitination, increases the acetylation, phosphorylation, stability and expression levels of p53, activates transcription of p53 target genes, and regulates cell proliferation, cell cycle, and apoptosis. AGGF1 also interacts with p53 through the FHA domain. Somatic AGGF1 variants in the FHA domain in human tumors, including p.Q467H, p.Y469 N, and p.N483T, inhibit AGGF1 activity on tumor suppression. These results identify a key role for AGGF1 in an AGGF1-MDM2-p53 signaling axis with important functions in tumor suppression, and uncover a novel trans -tumor-suppression mechanism dependent on p53. This study has potential implications in diagnosis and therapies of cancer. Highlights: Angiogenic factor AGGF1 is a novel-discovered tumor suppressor in cancers ex vivo and in vivo. AGGF1 can directly interact, acetylate, phosphorylate and stabilize p53 with its FHA domain. AGGF1 inhibits cancer cell growth through and dependent on p53 functions. AGGF1 somatic mutations in the FHA domain abolish the tumor suppressor function via losing the stabilizing effect on p53.